ANALISIS PUTUSAN PENGADILAN NEGERI KOTA SUKABUMI NOMOR 3/PID.SUS-ANAK/2023/PN SKB DALAM PERKARA KEKERASAN SEKSUAL TERHADAP ANAK - Firdaus, Muhammad Saddam; Juhana, Ujuh (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2024)
Sexual violence against children is an act of sexual harassment or coercion carried out against minors. These actions can include various forms, ranging from unwanted touching, sexual exploitation, to rape. This research aims to examine and analyze how the law is applied and the effectiveness of punishment in the decision of the Sukabumi City District Court Number 3/Pid.Sus-Anak/2023/PN.Skb. The type of research used is normative law with data sources in the form of interviews and observations, supported by literature study. The method used to process and analyze the data obtained was qualitative analysis with the research location being at the Sukabumi City District Attorney's Office and the Sukabumi City District Court. The research uses the theory of Child Legal Protection and the theory of the Juvenile Criminal Justice System. The results of the research explain that Children in Conflict with the Law were proven guilty of committing violence by forcing children to have sexual intercourse repeatedly, violating Article 81 paragraph (1) Jo. Article 76D of the Child Protection Law. Children in conflict with the law are sentenced to imprisonment at the Special Child Development Institute (LPKA) and job training. Overall, although this punishment has good intentions, its effectiveness has not been fully achieved because several aspects of implementation still need to be improved.